Polymorphism of HLA class I and class II alleles in influenza A(H1N1)pdm09 virus infected population of Assam, Northeast India. Issue 5 (5th February 2018) - Dutta, Mousumi; Dutta, Prafulla; Medhi, Subhash; Borkakoty, Biswajyoti; Biswas, Dipankar
Abstract : Human leucocyte antigen (HLA) represents one of the most highly polymorphic systems which plays a central role in the immune response. Genetic polymorphism of HLA in influenza A(H1N1)pdm09 infected population may be an important factor in disease progression and severity that needs further probing. In this study, a total of 110 Influenza like illness patients were recruited from the population of Assam, Northeast India, from which 35 cases infected by A(H1N1)pdm09 viruses and 35 controls were typed for HLA‐A, B and DRB1 locus by PCR‐SSP method. A total of seven alleles of HLA‐A, 16 alleles of HLA‐B, and 11 alleles of HLA‐DRB1 locus were identified. The most common alleles within each locus in cases were HLA‐A*11 (85.71%, P = 0.046), HLA‐B*35 (25%, P = 0.0001), and HLA‐DRB1*15 (49.35%, P = 0.133) as compared to the controls, HLA‐A*11 (40.82%), HLA‐B*35 (0.00%), and HLA‐DRB1*15 (67.53%). The frequency of HLA‐A*11 and HLA‐B*35 were significantly higher in cases as compared to the controls. In DRB1 locus, HLA‐DRB1*10 was significantly higher in cases (20.78%, P = 0.005) than that of controls (0.00%). Whereas, HLA‐DRB1*15 showed a higher frequency in controls than in cases. In addition, HLA‐DRB3*01 ( P = 0.053), DRB4*01 ( P = 1.000), and DRB5*01( P = 0.591) were also identified along with HLA‐DRB1 haplotype. From this preliminary study, it is suspected that there may be a role of HLA‐A*11, HLA‐B*35 and HLA‐DRB1*10 in conferring susceptibility to influenza A(H1N1)pdm09 infection in the study population. A larger extended study on HLA polymorphism may explain the association between HLA and influenza A(H1N1)pdm09 infection and provide insights for HLA restricted peptide based vaccines.